THE IMPLEMENTATION OF DIGITAL CHANNELS IN BUSINESS PROCESSES AND ACCESS TO FINANCE FOR MSMES IN AZERBAIJAN - Nazrin Akhundzada; Inara Rzayeva (Agora International Journal of Economical Sciences (AIJES), 2023)
Digitalization is assessed as a factor contributing to the sustainable growth of business entities. Implementation of digital solutions has been recognized as a key tool stimulating expansion and development of micro, small and medium enterprises into the economy. Micro small and medium enterprises represent a vast majority of firms in Azerbaijan. Limited access to financial resources is one of the key challenges exhibited by this size of enterprises. The rate of usage of online services by firms accelerated after COVID-19 pandemic. Despite significant progress during recent years, the adoption level of digital technologies particularly for financial services among population and entrepreneurs still needs to be developed. This article applies time series regression analysis and finds the existence of positive relationship between digitalization of business activities exemplified by e-commerce and the amount of credit funds allocated micro, small and medium business entities. The authors suggest about the existence of other factors that contribute to financial inclusion of small and medium-sized enterprises.
Keywords: 330